Russian credit organizations in the international system of counteracting income legalizing (laundering) and finance terrorism - I. V. Vashchekina (Plekhanov Russian University of Economics, 2018)
In order to counteract the shadow sector of economy, organized crime and terrorist attacks many countries set up systems of opposing criminal income laundering and terrorism financing, whose primary goal is finance monitoring. The first level of such systems forms associations of international status, the second level is occupied by national systems of CIL/FT, the third level is formed by certain finance and commercial organizations interacting with the first two. The Russian national system of CIL/FT is based on cooperation of Rosfinmonitoring, the Bank of Russia and other organizations, whose list is fixed by Russian legislation. They ensure the compliance of Russian credit organizations functioning with FATF recommendations, Wolfsberg principles and measures aimed at Basel AML-index of Russia. Struggle against laundering is one of the most important objectives of providing competitiveness of all Russian economy, as it fosters creation of positive investment climate, improves the international prestige of the country as a whole and strengthens its political positions.